Learning Styles among Students Pursing Entrepreneurship Course in Higher Education. - Chai, F. T.; Zaidatol, A. L. P.; Asimiran, Soaib; Jusoh, Rosnani (Pertanika Journal of Social Sciences & Humanities, 2013)
The purpose of the study was to identify the learning styles among entrepreneurship course students in higher education. The sample comprised of 270 students who had enrolled in Entrepreneurship Course as a compulsory course in their respective programme of studies at Universiti Putra Malaysia (UPM). Concrete Processing learning style was found to be the most preferred learning style. In particular, technical programme students, science programme students and literature programme students rated Concrete Processing as their most preferred learning styles. The findings of this study are encouraging and have shown a favourable development of entrepreneurship education in universities. The learning styles need to be identified clearly because there is a need to access and apply knowledge for problem solving purposes. They enable policy makers to know how the students learn, how they transform information to knowledge, and how they transfer new knowledge into applications. Students' learning styles can help lecturers to fully understand the learning process and also how a student acquires knowledge. As it can be recommended from the findings of this study, entrepreneurship education should focus on the learning of entrepreneurial competencies needed by the students who must be equipped to reproduce or acquire existing business. Learning entrepreneurial competencies can increase the interest and entrepreneurial intention of the students to choose entrepreneurship as a career. This can offer a solution for the current graduate unemployment problem in Malaysia.